Broadband access strategies: financing and governance. Issue 4 (2014) - John Frederiksen
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper was to present a number of issues regarding broadband access strategies in the coming years with at least four different competing broadband access forms. Pricing, investment and financing in relation to these issues are presented. The developments of interconnection and Internet governance are also presented. Design/methodology/approach – Description of trends for demand and supply for broadband access and the challenges for financing of the necessary investments. Findings – The most probable outcome for the coming decade is that a broadband access strategy is very dependent on where you believe the saturation level for the demand of bandwidth from normal residential household will be. Wireline and mobile wireless solutions will probably mainly be complements. Furthermore, there is a challenge for the whole telecommunication sector in relation to financing the necessary investments, because several factors are forcing the profit level in the sector downwards. The ongoing merger of two different interconnection regimes has an impact on the economy for network operators. Finally, the challenge of how to govern the Internet is emphasized. Originality/value – The paper provides a new structure for how to analyse the challenges for the telecom operators regarding choice of access strategy, financing of investments and governance.